Educación para la paz y cultura de paz en documentos internacionales - Carmen Labrador (Universidad de La Rioja, 2013)
The purpose to this paper is to know the contribution the International Organism, specially the Council of Europe and UNESCO, over education to the peace and culture of peace. The Declaration of Vienna, the Declaration of Budapest, the Transdisciplinary Proyect 'Toward: a Culture of Peace' and the Manifesto 2000 for a Culture of Peace and Non-Violence are the documents studied. The education of peace is considered to learned sperience in the societe pluricultural where the diference understand with tolerance, way of going abaut informed, reasonable and ethics. At the even of the new millennium, the General Assembly of the United Nations has proclaimed the year 2000 as the International Year for the Culture of Peace and the Decade 2001-2010 as the International Decade for the Children of the World. This is on acount of which invite to conceptual revisions at to decide that the peace only to get with our conduct, our attitude and our experience daily.